Upaya Meningkatkan Kemampuan Menghafal Ayat-Ayat Al-Qur’an Hadis Menggunakan Media Disk Murattal Al-Qur’an pada Siswa MTs. Swasta Tarbiyah Waladiyah Pulau Banyak - Maulida Maulida; Nurmisdaramayani Nurmisdaramayani ; Neni Anggraini (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
Focus of this research is that the researcher focuses on the application of Murattal Disk Media and the efforts made by the teacher in the field of Al-Qur'an Hadith studies to improve students' reasoning abilities. 1). The effect of digital Al-qur'an-based Murattal Disk Media on students' reasoning abilities on the concept of understanding and memorizing verses of the Qur'an by students of Madrasah Tsanawiyah Private Tarbiyah Waladiyah Pulau Banyak which is significant is that the application of the model helps students to better understand the subject matter. 2). The improvement of students' reasoning abilities on indicators of creative thinking, flexible thinking, original thinking, and detailed thinking after the Murattal Disk Media was applied to students of Madrasah Tsanawiyah Swasta Tarbiyah Waladiyah Pulau Banyak. 3). Student activities when the Murattal Disk Media was applied to the field of study of Al-qur'an Hadith at the Private Tarbiyah Madrasah Waladiyah Pulau Banyak, namely the students responded well. The approach and type of research used in the preparation of this research tool was classroom action research, namely